A case study on sustainable fabric manufacturing: Pattu weaving - Srivastava, Ankita; Saxena, Ankur (2022)
Sustainable materials, techniques, processes and disposal systems are becoming important to sustain the eco-system. From the last few decades unsustainable practices increases drastically due to imbalance of demand and supply, scarcity of resource, advent of unsustainable technologies among the other triggering factors. Traditionally, sustainable practices were integral part of the lifestyle of human beings including the manufacturing techniques for various product categories. Many ancient crafts clusters are still existing and re-inventing themselves to create sustainable products. The craft of ‘Pattu weaving’ is one of them which is known as a traditional weaving technique. Pattu weaving incorporates extra weft weaving technique which is widely practised by the weavers in India. Present study is focused on the materials, tools, techniques and processes used in this craft, along with the challenges and opportunities for the upliftment of the craft. A comparative study of traditional and contemporary materials, colour palette, motifs and product range of the craft are also covered in this paper. For this study, primary research is based on the information that have been collected during craft research documentation activity funded by Ministry of Textiles, India. Along with this, secondary research has also been included to strengthen the study.